Heat transfer analysis of a second grade fluid over a stretching sheet - C. E. Maneschy; M. Massoudi (International Journal of Mathematics and Mathematical Sciences)
The heat tranfer and flow of a non-Newtonian fluid past a stretching sheet is analyzed in this paper. Results in a non-dimensional form are presented here for the velocity and temperature profiles assuming different kind of boundary conditions.